Seasonal variation in food security, lifestyle, nutritional status and its associated factors of the urban poor adolescents in Kuala Lumpur, Malaysia: research protocol of a prospective cohort study - Tay, Janice Ee Fang; Tung, Serene En Hui; Kaur, Satvinder; Gan, Wan Ying; Che’Ya, Nik Norasma; Tan, Choon Hui (BioMed Central, 2023)
Background: Climate change, obesity and undernutrition have now become a worldwide syndemic that threatens most people’s health and natural systems in the twenty-first century. Adolescent malnutrition appears to be a matter of concern in Malaysia, and this is particularly relevant among the urban poor population. Mounting evidence points to the fact that underlying factors of malnutrition are subject to climate variability and profoundly affect nutritional outcomes. Hence, it is interesting to examine seasonal variation in nutritional status and its associated factors of urban poor adolescents in Malaysia.